EFL Learners’ Involvement in the Process of Learning: A Plea for an Active Classroom through Communicative Activities - MUBIKABALA, Damien IFALAMBANGA (International Journal of Scientific Research and Management (IJSRM), 2022)
English has become an international language among nations and serves as a “lingua franca”. For that reason, English is nowadays spoken, studied and even understood in countries where it is not the first language. There is an increased interest regarding the importance of that language around the world. Therefore, many want to learn and study it.However, one of the needs in the learning and teaching of a foreign language aims at developing the four basic, skills that is listening, speaking, reading and writing. But speaking has a crucial importance like all the other skills. These competencies are not well developed because of factors such as the number of pupils in a class, lack of learning resources, and lack of opportunities which lead pupils to not communicate, the exaggerated use of grammar and classroom language centered by the teacher, which does not motivate pupils in the learning process. I also emphasize the teacher’s attitude and the choice of techniques, strategies and methods that can help learner to master the language.Therefore, this work gives the importance of communicative activity as a way to help pupils acquire communicative competence in the learning of English as a Foreign Language by pupils in our secondary schools in general and particularly those of Bandundu town secondary schools.